Biological Significance of the Importin‐β Family‐Dependent Nucleocytoplasmic Transport Pathways. (23rd May 2014) - Kimura, Makoto; Imamoto, Naoko
<x xml:space="preserve">Abstract</x> Importin‐β family proteins (Imp‐βs) are nucleocytoplasmic transport receptors (NTRs) that import and export proteins and RNAs through the nuclear pores. The family consists of 14–20 members depending on the biological species, and each member transports a specific group of cargoes. Thus, the Imp‐βs mediate multiple, parallel transport pathways that can be regulated separately. In fact, the spatiotemporally differential expressions and the functional regulations of Imp‐βs have been reported. Additionally, the biological significance of each pathway has been characterized by linking the function of a member of Imp‐βs to a cellular consequence. Connecting these concepts, the regulation of the transport pathways conceivably induces alterations in the cellular physiological states. However, few studies have linked the regulation of an importin‐β family NTR to an induced cellular response and the corresponding cargoes, despite the significance of this linkage in comprehending the biological relevance of the transport pathways. This review of recent reports on the regulation and biological functions of the Imp‐βs highlights the significance of the transport pathways in physiological contexts and points out the possibility that the identification of yet unknown specific cargoes will reinforce the importance of transport regulation. <inline-graphic xlink:href="ark:/27927/pghmhz09ct" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />